Update on LibQUAL+ 2004: the international library satisfaction survey instrument - Lock, Selena A. (Cranfield University, 2011)
Following from the success of the 2003 LibQUAL+ UK Pilot, SCONUL's Advisory Committee on Performance Improvement (ACPI) are coordinating a consortium of SCONUL libraries in LibQUAL+ 2004. LibQUAL+ is a World Wide Web based library users survey, measuring their minimum, perceived, and desired levels of service quality. It assesses three core dimensions of library service: information control (questions on, for example, availability of resources and the ability to access them); affect of service (questions concerning the effectiveness of library staff); and library as place (questions on the physical environment). Following calls for participation circulated by email in September 2003, a total of 17 institutions (university libraries) registered to run the LibQUAL+ survey in 2004 and they are listed. (Quotes from original text)
Keywords: Library management; User satisfaction; Evaluation; Performance measures; Quality; LibQUAL+; User surveys